Neurobehavioral symptom validity in U.S. Department of Veterans Affairs (VA) mild traumatic brain injury evaluations. Issue 4 (21st April 2019) - Ashendorf, Lee
ABSTRACT: Introduction : The use of the Neurobehavioral Symptom Inventory (NSI) by U.S. Department of Defense and Veterans Affairs (VA) providers for all mild traumatic brain injury (mTBI) evaluations led to the development of methods to screen for symptom exaggeration. The present study was designed to explore the clinical utility of three metrics—the Validity–10 scale, the NSI total score, and the mild Brain Injury Atypical Symptoms Scale (mBIAS)—relative to the results of several different criterion measures of symptom validity. Method : Participants in this study were 82 U.S. military veterans referred for evaluations by a VA polytrauma clinic in the context of a history of mTBI. All participants were administered the Minnesota Multiphasic Personality Inventory–Second Edition–Restructured Form (MMPI–2–RF), NSI, and mBIAS. Results : None of the three scales displayed adequate accuracy at predicting failure on cognitive performance validity tests or on the MMPI–2–RF Fp-r scale. For the remaining MMPI–2–RF overreporting indices (F-r, Fs, FBS-r, RBS) and for an index based on elevation of any single MMPI–2–RF overreporting index, both the NSI total score and Validity–10 displayed high positive predictive power with adequate to good sensitivity values (39% to 76%). Conclusion : These findings support the use of Validity–10 and NSI total score as symptom validity tests (SVTs) that can be used to assess for neurobehavioral symptom exaggeration.